Environmental accounting, sustainability and accountability - Debnath, Somnath (Mathura Road SAGE Publications Private Limited, 2019)
The study of the interactions between business organizations and their natural environments has gained momentum recently under the aegis of social and environmental accounting and reporting (SEAR), and as a diluted form of response in corporate social responsibility (CSR), Environmental Accounting, Sustainability and Accountability, envisages accounting as an effective instrument in improving this interrelationship. It comprehensively describes how organizations can capture their environmental performance and thereby address societal concerns. The book closely explores how organizations can embed care for the environment as fundamental to their functioning. It broadly covers traditional accounting as a measuring instrument, contemporary advances and unresolved problems, alternative perspectives and recent developments. The central idea proposed here is to evolve the environmental accounting framework and bring calculative aspects into sustainability thinking that businesses are responsible for. Among the other important innovative ideas discussed are new costing techniques for waste management, accounting schematics of carbon trade, green information needs of management and the extension of the environmental viewpoint to information systems and technology
Title from title screen (viewed October 19, 2023)
Includes bibliographical references and index.
Description based on XML content
Keywords: Social responsibility of business; Business -- Environmental aspects